Effect of low fluence radiation on nanocomposite thin films of Cu nanoparticles embedded in fullerene C60. (August 2017) - Inani, Heena; Singhal, Rahul; Sharma, Pooja; Vishnoi, Ritu; Aggarwal, S.; Sharma, G.D.
Abstract: Metal-fullerene nanocomposite thin films with low concentration of Cu metal embedded in fullerene matrix have been synthesized using thermal co-deposition method. An ion irradiation with 120 MeV Ag ions beam was performed to assess the radiation effects for Cu (3%)-C60 nanocomposites at different fluences 1 × 10 12, 6 × 10 12, 1 × 10 13 and 3 × 10 13 ions/cm 2 . Optical properties and surface morphology of nanocomposite thin films were studied using UV-visible spectroscopy and atomic force microscopy, respectively. Absorption spectra demonstrated that absorption intensity of nanocomposite thin film was increased and modes of fullerene were diminished with fluence. The thickness of the film and atomic metal fraction in matrix were estimated by Rutherford backscattering spectroscopy and found to be ∼45 nm and 3%, respectively. Transmission electron microscopy was performed for structural and particle size evaluation of Cu nanoparticles (NPs) in matrix at higher fluence. Structural evolution of copper-fullerene C60 nanocomposite thin films with increasing fluence of 120 MeV Ag ion beam was studied by Raman Spectroscopy, which confirmed the amorphization of matrix (fullerene C60 ) at higher fluence. Highlights: Cu-C60 nanocomposite thin films are synthesized with small sized Cu nanoparticles using thermal co-evaporation. Films are investigated under 120 MeV Ag ion beam irradiation at different fluence. The modifications in optical, structural and morphological properties of metal-fullerene nanocomposites have been studied under swift heavy ion irradiation. The transformation of fullerene C60 into amorphous carbon is observed at a fluence of 3 × 10 13 ions/cm 2 .